Strategies Of Islamic Religious Education Teachers In Strengthening Students' Religious Character The Digital Era In Senior High School 1 Tapango - Lathiefatul Aghniyah; Sibawaihi Sibawaihi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
Abstract : The advancement of digital technology has transformed students' learning patterns while simultaneously presenting challenges for strengthening religious character. High levels of engagement with social media, digital games, and various internet platforms influence students' behavior, values, and moral awareness, requiring Islamic Religious Education teachers to adopt adaptive educational strategies. This study aims to analyze the strategies employed by Islamic Religious Education teachers at SMAN 1 Tapango to strengthen students' religious character in the digital era. The study utilizes a field research approach with a descriptive qualitative method. Data were collected through observation, interviews, and documentation, and subsequently analyzed using qualitative descriptive techniques. The findings reveal that Islamic Religious Education teachers implement four primary strategies: habituating religious activities, modeling religious behavior, supervising and guiding social media usage, and fostering collaboration between the school and parents. The success of these strategies is supported by school policies and the active involvement of the principal, teachers, and parents; conversely, excessive use of social media and digital games, along with low student participation in religious activities, serve as major obstacles. The study concludes that strengthening religious character in the digital era requires an integrated approach combining habituation, role modeling, digital guidance, and sustained cooperation between schools and families to ensure that technological advancements are positively leveraged in shaping students' religious character. Keywords: Islamic Religious Education Teacher; Religious Character; Digital Era; Students.